Evaluation of the PHBS Program For 2018, 2019, and 2020 In Masalle Village, Enrekang Regency - Haderiah Haderiah; Muhammad Ikbal Arif; La Taha La Taha; Sulasmi Sulasmi; Hidayat Hidayat (Green Publisher Indonesia, 2022)
PHBS is all healthy behaviors that are carried out on the basis of awareness to help themselves and family members in the health sector and can play an active role in carrying out public health activities. Clean culture is a reflection of people's attitudes and behavior in maintaining and maintaining personal and environmental hygiene in everyday life. The PHBS indicators that are the center of this research are healthy latrines, clean water supply, hand washing with soap, and smoking habits.This study aims to evaluate the PHBS program in the village of Masalle, Enrekang Regency. This type of research is a descriptive research which describes, discloses and presents what is in accordance with the data and facts regarding the PHBS program that has been launched. The number of samples was 4 PHBS indicators, namely healthy latrines, clean water supply, washing hands with soap, and smoking habits.The results obtained from the results of the PHBS study in Masalle Village, namely in 2018, the indicators for healthy latrines were 94.0%, PAB was 100%, CTPS was 99.1%, smoking habits were 53.3%. In 2019 the indicators for healthy latrines were 94.8%, PAB was 100%, CTPS was 100%, smoking habits were 53.3%. In 2020 the indicators for healthy latrines are 95.3%, PAB is, CTPS is 100%, smoking habits are 53.3%.